Development of Hand Grip Assistive Device Control System for Old People through Electromyography (EMG) Signal Acquisitions - Shahrol, Mohamaddan; Herman, Khamis; Komeda, Takashi; Aidil Azli, Alias; Shirley, Jonathan Tanjong; Norhuzaimin, Julai; Nurul Izzati, Hashim (EDP Sciences, 2017)
The hand grip assistive device is a glove to assist old people who suffer from hand weakness in their daily life activities. The device earlier control system only use simple on and off switch. This required old people to use both hand to activate the device. The new control system of the hand grip assistive device was developed to allow single hand operation for old people. New control system take advantages of electromyography (EMG) and flex sensor which was implemented to the device. It was programmed into active and semi-active mode operation. EMG sensors were placed on the forearm to capture EMG signal of Flexor Digitorum Profundus muscle to activate the device. Flex sensor was used to indicate the finger position and placed on top of the finger. The signal from both sensors then used to control the device. The new control system allowed single hand operation and designed to prevent user from over depended on the device by activating it through moving their fingers.